(untitled) - Mangale, Mpatla Blessing

Investigation on the functional role of two mycobacterium smegmatis gene products on heme O biosynthesis and translocation (Stellenbosch : Stellenbosch University, 2023)
Mangale, Blessing. 2023. Investigation on the functional role of two mycobacterium smegmatis gene products on heme O biosynthesis and translocation. Unpublished master's dissertation. Stellenbosch : Stellenbosch University [online]. Available at: https://scholar.sun.ac.za/items/4e0b0f5e-6dcf-4bb3-a4cb-2d2bd70e27ab